The association between relative fat mass (RFM) and lumbar bone density in US adults: Insight from 2011–2018 NHANES - Hanwen Zhang; Jian Mei (PLoS ONE, 2025)
Background The relationship between obesity and osteoporosis has been widely studied. Studies have shown that relative fat mass (RFM) can be used to predict obesity. However, its relationship with bone mineral density (BMD) is unclear. The aim of this study was to investigate the relationship between RFM and lumbar BMD. Methods We used data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. Multiple linear regression models were applied to examine the relationship between RFM and lumbar BMD. We used smoothed curve fitting and threshold effect analysis to check for non-linear trends. Subgroup analyses were performed to explore differences in various populations. The Receiver operating characteristic (ROC) curve was used to evaluate the diagnostic potential of body mass index (BMI), weight-adjusted waist circumference index (WWI), waist circumference (WC), and RFM for OP. Results A total of 10636 participants were included. Multiple linear regression showed a significant negative link between RFM and lumbar BMD. In subgroup studies and smoothed curve fitting, RFM was consistently associated with lower BMD across subgroups. ROC curve indicate that RFM is more sensitive than BMI, WWI and WC in diagnosing OP capacity. Conclusion RFM is negatively associated with lumbar BMD in US adults. This suggests that RFM contributes to the study of low BMD.